The Influence of Age, Tenure, Education and Gender of the Corporate Secretary on Company Performance on the IDX - Moh. Baqir Ainun; Nur Qoudri Wijaya; Liyanto Liyanto (Journal of Research in Social Science and Humanities, 2024)
Financial Services Authority Regulation Number 35 of 2014 states that a company secretary is mandatory for public companies. they will realize GCG and be responsible for the processes and performance of the board of directors and firm performance. Literature on the influence of corporate secretaries on firm performance is limited. However, based on upper echelon theory, the characteristics of the company secretary need to be considered because they describe their performance and their effect on firm performance. Therefore, this study aims to examine the influence of company secretary characteristics on firm performance. The sample used was companies registered on the BEI for the 2018-2022 period with 944 observations. The results of multiple linear regression analysis show that age and education have an effect on firm performance, while tenure and gender have no effect on firm performance. The results add to the literature on the characteristics of corporate secretaries and firm performance, and provide important information that corporate secretaries need to pay attention to.